Efektivitas Kombinasi Minyak Biji Pala dan Infusa Daun Teh Hijau Sebagai Antidemensia Pada Mencit Terinduksi Atropin Sulfat - Gentala Yodha Prawira; Yovita Mercya (JURNAL FARMASI DAN MAKANAN, 2026)
Cognitive impairment is associated with decreased cholinergic system activity and can be acutely modeled using atropine sulfate as a muscarinic receptor antagonist. This study aimed to evaluate the effectiveness of a combination of nutmeg essential oil (Myristica fragrans) and green tea leaf infusion (Camellia sinensis) on memory function in atropine-induced male mice. A quasi-experimental pretest–posttest control group design was used involving 30 mice divided into six groups. The observed parameter was escape latency in the Morris Water Maze test. The results showed that all groups had relatively homogeneous baseline learning ability, indicated by a progressive decrease in escape latency during the training phase. Atropine sulfate induction significantly increased escape latency in the negative control group (p = 0.043), indicating cognitive impairment. The combination of nutmeg essential oil and green tea leaf infusion significantly reduced escape latency compared to the post-induction condition (p = 0.043). However, no significant differences were observed between the combination and single treatments (p = 0.083) or compared to the positive control donepezil (p = 0.175). It can be concluded that the combination has the potential to improve cognitive function with effectiveness comparable to standard therapy.